Freshwater microbiology : perspectives of bacterial dynamics in lake ecosystems - Bandh, Suhaib A.; Shafi, Sana; Shameem, Nowsheen (Academic Press, an imprint of Elsevier, 2019)
"Freshwater Microbiology: Perspectives of Bacterial Dynamics in Lake Ecosystems provides a comprehensive and systematic analysis of microbial ecology in lakes. It offers basic information on how well the bacterial community composition varies along the spatio-temporal and trophic gradients along with the evaluation of the bioindicator species of bacteria so as to act as a key to predict the trophic status of lake ecosystems. The book helps to identify the factors of potential importance in structuring the bacterial communities in lakes as it delves into the dynamics and diversity of bacterial community composition in relation to various water quality parameters. It helps to identify the possibility of bioremediation plans and devising future policy decisions, with better conservation and management practices."--